Medial unicompartmental arthroplasty. A survival study of the Oxford meniscal knee. - Carr, A; Keyes, G; Miller, R; O'Connor, J; Goodfellow, J (1993)
One hundred twenty-one knees with medial compartment osteoarthrosis were treated by unicompartmental arthroplasty with the Oxford Knee. The strict selection criteria were (1) the presence of a functioning anterior cruciate ligament, (2) fully correctable deformity, and (3) full thickness of articular cartilage in the lateral compartment. The mean elapsed time from surgery was 44.4 months. One knee has required revision for a loose tibial component. The results at this stage are as acceptable as those of tricompartmental knee arthroplasty and better than those of high tibial osteotomy.